Homocysteine metabolism in children and adolescents with epidermolysis bullosa - De Giuseppe, Rachele (BMC Pediatr, 2016)
BACKGROUND: Epidermolysis bullosa (EB) belongs to a family of rare heterogeneous, genetic disorders characterized by blistering of the skin and mucous membranes in response to minor mechanical trauma. The involvement of the oral mucosa and oesophagus stenosis is suggested to be responsible for severe nutritional deficiencies, but few studies have till now considered this aspect. This observational study aimed to evaluate homocysteine status in children and adolescents with EB by assessing total plasma homocysteine (tHcy) and metabolically related vitamins (B(6), B(12), folate) concentrations. METHODS: Twenty EB patients (12 M; age range 0.5−19 years) were evaluated for: plasma tHcy, serum B(12) and holotranscobalamin (HoloTC, the active fraction of B(12)), serum and erythrocyte folate (s-F and Ery-F, respectively), plasma B(6) and serum high sensitive C-reactive-protein (hsCRP) levels. Clinical severity was also evaluated through the Birmingham Epidermolysis Bullosa Severity (BEBS) score. A sex and age well-matched population was also enrolled. RESULTS: EB patients showed tHcy levels higher (p = 0.04) and B(6) levels lower (p = 0.03) than controls. B(12), HoloTC, s-F and ery-F concentrations did not differ between patients and controls. Multiple linear regression analysis showed that tHcy levels were independent of the metabolically related vitamins levels. In addition, serum hsCRP levels were higher in EB patients than in controls (p = 0.003) and correlated negatively with B(6) concentrations (r = -0.6; p = 0.009). BEBS score correlated negatively with HoloTC (p = 0.022) and B(6) (p = 0.005) levels and positively with age (p = 0.031) and hsCRP levels (p < 0.001). CONCLUSIONS: The assessment of tHcy and metabolically related vitamin levels describes an important aspect of EB patients’ nutritional status which can result essential for their long term care. Monitoring B(6) levels in EB patients could be particularly important in order to prevent several complications associated with B(6) deficiency and to avoid a B(6) excess which sustains an inflammatory condition.